# If E and F are events such that $P(E) = \dfrac{1}{4},P(F) = \dfrac{1}{2}{\text{ and P(E}} \cap {\text{F) = }}\dfrac{1}{8}$find:

$(1){\text{ P(E }} \cup {\text{ F)}}$

$(2){\text{ P}}\left( {\overline E \cap \overline F } \right)$Or $P\left( {{E^1} \cap {F^1}} \right)$

Answer

Verified

365.1k+ views

Hint- Use the formulae for ${\text{P(E }} \cup {\text{ F)}}$ in the first part and use the concept of De Morgan’s law in the second part.

We have given, $P(E) = \dfrac{1}{4},P(F) = \dfrac{1}{2}{\text{ and P(E}} \cap {\text{F) = }}\dfrac{1}{8}$

$(1)$We know that${\text{P(E }} \cup {\text{ F)}} = P(E) + P(F) - P(E \cap F)$…………….. (1)

On substituting the values in equation (1) we get

${\text{P(E }} \cup {\text{ F)}} = \dfrac{1}{4} + \dfrac{1}{2} - \dfrac{1}{8} = \dfrac{{2 + 4 - 1}}{8} = \dfrac{5}{8}$

$(2)$Now from the solution of first part we know that

${\text{P(E }} \cup {\text{ F) = }}\dfrac{5}{8}$………………………………. (2)

Now using De Morgan’s law ${\left( {E \cup F} \right)^1} = \left( {{E^1} \cap {F^1}} \right)$

$ \Rightarrow P{\left( {E \cup F} \right)^1} = P\left( {{E^1} \cap {F^1}} \right)$……………………….. (3)

Now $P{\left( {E \cup F} \right)^1} = 1 - P\left( {E \cup F} \right)$ (As $P(\overline {E)} = 1 - P(E)$

So using equation (2)

$P{\left( {E \cup F} \right)^1} = 1 - \dfrac{5}{8} = \dfrac{3}{8}$

Using equation (3) we can say that

$ \Rightarrow $ $P\left( {{E^1} \cap {F^1}} \right) = \dfrac{3}{8}$

Note- Whenever we face such types of problems we need to have a good grasp of formula as these are mostly formula based only. Some of the important formulas and theorems are being stated above. The physical interpretation of ${\text{P(E }} \cup {\text{ F)}}$is that we need to find the probability of occurring of event E or F. The physical interpretation of ${\text{P}}\left( {\overline E \cap \overline F } \right)$is probability of neither event E occurring and nor event F occurring.

We have given, $P(E) = \dfrac{1}{4},P(F) = \dfrac{1}{2}{\text{ and P(E}} \cap {\text{F) = }}\dfrac{1}{8}$

$(1)$We know that${\text{P(E }} \cup {\text{ F)}} = P(E) + P(F) - P(E \cap F)$…………….. (1)

On substituting the values in equation (1) we get

${\text{P(E }} \cup {\text{ F)}} = \dfrac{1}{4} + \dfrac{1}{2} - \dfrac{1}{8} = \dfrac{{2 + 4 - 1}}{8} = \dfrac{5}{8}$

$(2)$Now from the solution of first part we know that

${\text{P(E }} \cup {\text{ F) = }}\dfrac{5}{8}$………………………………. (2)

Now using De Morgan’s law ${\left( {E \cup F} \right)^1} = \left( {{E^1} \cap {F^1}} \right)$

$ \Rightarrow P{\left( {E \cup F} \right)^1} = P\left( {{E^1} \cap {F^1}} \right)$……………………….. (3)

Now $P{\left( {E \cup F} \right)^1} = 1 - P\left( {E \cup F} \right)$ (As $P(\overline {E)} = 1 - P(E)$

So using equation (2)

$P{\left( {E \cup F} \right)^1} = 1 - \dfrac{5}{8} = \dfrac{3}{8}$

Using equation (3) we can say that

$ \Rightarrow $ $P\left( {{E^1} \cap {F^1}} \right) = \dfrac{3}{8}$

Note- Whenever we face such types of problems we need to have a good grasp of formula as these are mostly formula based only. Some of the important formulas and theorems are being stated above. The physical interpretation of ${\text{P(E }} \cup {\text{ F)}}$is that we need to find the probability of occurring of event E or F. The physical interpretation of ${\text{P}}\left( {\overline E \cap \overline F } \right)$is probability of neither event E occurring and nor event F occurring.

Last updated date: 27th Sep 2023

•

Total views: 365.1k

•

Views today: 5.65k

Recently Updated Pages

What do you mean by public facilities

Slogan on Noise Pollution

Paragraph on Friendship

Disadvantages of Advertising

Prepare a Pocket Guide on First Aid for your School

What is the Full Form of ILO, UNICEF and UNESCO

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Summary of the poem Where the Mind is Without Fear class 8 english CBSE

The poet says Beauty is heard in Can you hear beauty class 6 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

What is the past tense of read class 10 english CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE